Effects of exposure to event 176 Bacillus thuringiensis corn pollen on monarch and black swallowtail caterpillars under field conditions - Zangerl, A. R. (The National Academy of Sciences, 2001)
The widespread planting of corn genetically modified to produce Bacillus thuringiensis endotoxin has led to speculation that pollen from these fields might adversely affect nearby nontarget lepidopterans. A previous study of Bt corn engineered with Monsanto event 810 failed to detect an effect of pollen exposure on the black swallowtail, Papilio polyxenes, in either the field or the laboratory. Here, we report results of a field study investigating the impact of exposure to pollen from a Bt corn hybrid containing Novartis event 176 on two species of Lepidoptera, black swallowtails and monarch butterflies, Danaus plexippus. Nearly half of the 600 monarch larvae died within the first 24 h; this and subsequent mortality was not associated with proximity to Bt corn and may have been due in part to predation. Survivorship of black swallowtails was much higher than that of the monarchs and was also independent of proximity to the transgenic corn. However, despite five rainfall events that removed much of the pollen from the leaves of their host plants during the experiment, we observed a significant reduction in growth rates of black swallowtail larvae that was likely caused by pollen exposure. These results suggest that Bt corn incorporating event 176 can have adverse sublethal effects on black swallowtails in the field and underscore the importance of event selection in reducing environmental impacts of transgenic plants.